Navigating the Labor Market among People Who Use Drugs: Qualitative Evidence from a Justice-Involved Sample - Mike Vuolo; Anneliese Ward; Lesley E. Schneider (Socius)
Given substantially higher substance use rates among justice-involved people and that employers are largely protected from disqualifying people who use drugs, the U.S. Department of Labor called for incorporation of substance use recovery into the “second chance” hiring framework for individuals with criminal records. Despite this call and a sizable literature on applicants navigating the market with a criminal record, the labor market experiences among the subset who use substances has not been directly studied. The authors address this research gap using 43 in-depth interviews with people with criminal records in central Ohio who use substances. With substance use taking primacy over possessing a record, two thematic approaches emerged. First, participants remained in the formal labor market by restricting applications to employers not conducting drug screens, along with avoiding triggering jobs and using evasion techniques. Second, participants described disconnecting from the labor market while using, either generating illegal income or describing addiction as too all encompassing to work. These results demonstrate that the restrictive labor market for people with criminal records is further limited among those who use substances and how substance use can prohibit labor market attachment. The authors describe implications for employment policy and the punitive nature of substance use control.